ANALISIS PENERAPAN SIKLUS AKUNTANSI PADA OMAH KARKAS - Asmarawati, Budi; Nurtyatimah, Nurtyatimah; Yustrianthe, Rahmawati (Jurnal Edueco, 2023)
This research aims to determine and analyze the accounting cycle in one of the MSMEs, namely, Omah Karkas. For this reason, the object of this research is the accounting cycle implemented by Omah Karkas. This type of research is qualitative, descriptive type. Data collection techniques were carried out using interviews, observation and documentation. Meanwhile, data analysis techniques start from organizing (reducing and selecting relevant data), presenting data (using data triangulation), interpreting and drawing conclusions. The results of this research indicate that Omah Karkas has carried out financial records. However, the financial records that have been carried out are quite simple